1995
DOI: 10.1111/j.1570-7458.1995.tb01965.x
|View full text |Cite
|
Sign up to set email alerts
|

Cleome monophylla essential oil and its constituents as tick (Rhipicephalus appendiculatus) and maize weevil (Sitophilus zeamais) repellents

Abstract: The repellency of the essential oil of the shrub Cleome monophylla (Family: Capparidaceae) and identified constituents of the oil were evaluated against the livestock tick, Rhipicephalus appendiculatus and the maize weevil, Sitophillus zeamais. In a tick climbing repellency bioassay, the oil of C. monophylla exhibited repellency which, at the highest dose, was comparable to that of the commercial arthropod repellent N, N‐diethyl toluamide (DEET). In a Y‐tube olfactometer bioassay, C. monophylla oil showed high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 12 publications
2
50
0
2
Order By: Relevance
“…However, products from this plant species can cause detrimental effects on natural enemies in storage environments (Sanon et al 2011), thus requiring caution when used as grain protectants. In addition, other plant species of the Cleome genus showed repellent actions against ticks (Parasitiformes) and insects (Ndungu et al 1995;Nyalala & Grout 2007), but the present study is the first to report on the insecticidal/repellent potential against C. spinosa.…”
Section: Repellent Activitiesmentioning
confidence: 82%
“…However, products from this plant species can cause detrimental effects on natural enemies in storage environments (Sanon et al 2011), thus requiring caution when used as grain protectants. In addition, other plant species of the Cleome genus showed repellent actions against ticks (Parasitiformes) and insects (Ndungu et al 1995;Nyalala & Grout 2007), but the present study is the first to report on the insecticidal/repellent potential against C. spinosa.…”
Section: Repellent Activitiesmentioning
confidence: 82%
“…Previous studies of long chain aliphatic methyl ketones showed repellence to arthropods, including blood sucking insects (Ndungu et al, 1995;Blum, 1966;Torr et al, 1996;Barton, 2003;Roe, 2004;Gikonyo et al, 2002;). For example, repellency activities of 2-decanone, 2-undecanone and 2-dodecanone to Glossina morsitans morsitans have been recorded in wind tunnel experiments (Gikonyo et al, 2003).…”
mentioning
confidence: 99%
“…The use of African plant oils and resins to control tick pests through repellency, immobilization or acaricidal activity has been studied elsewhere. The essential oil of molasses grass, Melinis minutiflora, has been shown to repel the brown-ear tick, Rhipicephalus appendiculatus (Mwangi et al, 1995), as has the essential oil of the shrub, Cleome monophylla (Ndungu et al, 1995), Ce. hirta , and the East African shrub, Gynandropsis gynandra .…”
Section: Discussionmentioning
confidence: 99%